Pivoting the self : Gendered identity construction of impoverished women transitioning from paid work to entrepreneurship in rural Indonesia - Ginting-Szczesny, Bernadetta Aloina; Kibler, Ewald; Hytti, Ulla (Sage, 2026)
In this article we develop a situated understanding of how impoverished women entrepreneurs embark on gendered identity construction as they transition from paid employment to entrepreneurship. Drawing on self-narratives of 31 rural Indonesian women entrepreneurs previously employed as migrant domestic workers, we examine how they navigate this transition and construct their identities around entrepreneurship and socio-cultural norms. The concept of identity-pivoting work is introduced, through which women reorient themselves upon their return to structural gendered subordination embedded in their local communities. Four forms of identity-pivoting are identified and discussed – realigning, resigning, reclaiming, and reforming – which differ based on the positioning of past employment and gendered family roles in relation to current entrepreneurial activities. We conclude by explicating how our insights advance the knowledge on gendered dynamics in the construction of entrepreneurial identities upon transition from employment to entrepreneurship.